A REVIEW ON FORMULATION OF ZINGIBER OFFICINALE ESSENTIAL OIL - Vikram Kumar; Bhagwati Devi; Tina Bhardwaj; Harish Kumar; Aman (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Zingiber officinale, commonly known as ginger, is a rhizome that has been used as a healthy herbal plant for centuries. Used for thousands of years in traditional medicine, ginger is known for their beneficial health effects. Zingiber officinale has complex composition of bioactive constituents, including essential oils, phenolic compounds, and oleoresins contributing to their therapeutic benefits. These major constituents are responsible for the wide-ranging pharmacological actions of ginger, including anti-inflammatory, antioxidant, and antimicrobial activities, which further emphasize the significance of ginger in both traditional and modern medicine. More specifically, gingerol, its main active ingredient, has been proven to relieve nausea and vomiting, particularly in pregnant women and patients that get chemotherapy. Its essential oil data was formulated and may serve useful in developing various degrees and therapeutic formulations (especially transdermal). Though ginger essential oil is achieved with many challenges such as extremely volatile, low solubility in water, the studies show the implementation of innovative solutions like the use of nanoemulsion techniques. In a different study, lower droplet sizes were observed using the spontaneous emulsification method with surfactants like Tween 80, promoting stability of the oil. Continued investigation into the most effective formulation strategies remains critical for extracting the potential therapeutic properties of Z. officinale essential oil providing a pathway for the incorporation of this natural product into modern health applications.